GROWTH OF ORNAMENTAL PEPPER IN COLORED CONTAINERS UNDER PROTECTED ENVIRONMENTS - Costa, Edilson; Alixame, Daniell; Silva, Abimael G. da [UNESP]; Pupim, Rafael de S.; Binotti, Flavio F. da S. (Soc Brasil Engenharia Agricola, 2020)
Ornamental pepper plants produced in containers under protected environments have high added value. We carried out research with an aim to evaluate the growth and development of ornamental pepper in containers of different colors under two protected environments, both with thermal-reflective screens under a polyethylene film: one with 18-22 % shading and the other with 42-50 % in colored containers (brown, blue, black, and red). The treatments formed by a 2 x 4 factorial (environments x container colors) were arranged in a completely random pattern with 4 replications and 5 plants per plot, and a joint analysis of experiments was used to compare environments. The protected environment covered with low-density polyethylene film having 42-50 % of shading promoted higher initial growth of pepper plants, including early maturity, compared to the protected environment with 18-22 % of shading. The colored containers, namely, the brown container in a protected environment with 42-50 % shading and red container with 1822 % shading formed plants with better growth and yield characteristics compared to the black container. The seedlings in the blue container had delayed flowering.
Keywords: Capsicum frutescens; plant ambiance; pot colors